The hematopoietic function, histological characteristics, and transcriptome profiling of Wanxi white geese ovary during nesting and late-laying stages - Chunfang Zhao; Tao Jin; Kefeng Yang; Xinyu Liu; Man Ren; Deyong She; Qianqian Hu; Shenghe Li (Poultry Science)
Despite several factors influencing reproduction in geese, but the precise molecular mechanisms of egg cessation are not fully understood. In the present study, the hematopoietic parameters and serum hormone levels in Wanxi white geese were analyzed. RNA-Seq was utilized to identify the differentially expressed mRNAs (DEGs) and lncRNAs (DE lncRNAs) in the ovarian tissues associated with nesting in geese during the late-laying and nesting periods. Triglyceride (TG) and alkaline phosphatase (ALP) levels were higher in late-laying geese, while white blood cell (WBC), neutrophil (NEU), hemoglobin (HGB), and hematocrit (HCT) levels were significantly lower in late-laying geese. Serum levels of luteinizing hormone (LH), estrogen (E2), and progesterone (P4) increased significantly during the late-laying period, whereas prolactin (PRL) level was lower in the late-laying period than the nesting period. During the late-laying period, geese had a clear follicular hierarchy, with ovaries exhibiting mature and primary follicles. In the nesting period, the ovaries were degenerated and had many primary follicles without follicular development. Analysis of mRNA-lncRNA expression revealed 1,257 DEGs between the nesting and the late-laying stages, of which 841 were up-regulated and 416 were down-regulated DEGs. A total of 340 DE lncRNAs were identified between the nesting and the late-laying periods, with 113 being up-regulated and 227 down-regulated lncRNAs. DEGs, including TMEM, DRD3, IGFBP7, MAPK13, GnRHR2, HECTD3, KCNU1, OPRD1, and VCAM1, along with DE lncRNAs, including XR_001203613.1, XR_001206155.1, XR_001207759.1, XR_001213571.1 and XR_001214368.1 participate in reproduction in geese. Correlation analysis indicated that the cis-regulation of XR_001213096.1-ITPR3, XR_001203613.1-GALNT15, XR_001206155.1-COL6A3, XR_001207759.1-ANKS1B, and XR_001214368.1-VPS45 participate in the molecular mechanisms underlying nesting in geese. Functional enrichment analysis revealed the DEGs and DE lncRNAs associated with focal adhesion, extracellular matrix (ECM)-receptor interaction, cell adhesion molecules (CAMs), and PI3K-Akt signaling pathways, were responsible for the differences in the ovaries between the nesting and late-laying periods. This study offers valuable information on the roles of genes and lncRNAs, and the mechanisms underlying variations in reproductive performance between the late-laying and nesting periods.